PENGEMBANGAN MEDIA KOCIBANTAR PADA PEMAHAMAN KONSEP CIRI-CIRI BANGUN DATAR KELAS IV DI SD - Pou, Fuspawati; Husain, Rustam I; Marshanawiah, Andi; Aries, Nur Sakinah; Pulukadang, Wiwy Triyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This development research aims to comprehensively describe the design and validation process of innovative learning media called